ANALISIS DISIPLIN KERJA APARATUR SIPIL NEGARA (ASN) PADA SEKRETARIAT DEWAN PERWAKILAN RAKYAT ACEH - Kamaruzzaman, Kamaruzzaman; Ningtyas, Ajeng Purwati (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2025)
This study aims to understand how work discipline among Civil Servants (ASN) is developed and maintained within the Secretariat of the Aceh Regional House of Representatives. Work discipline is considered essential for creating a professional and integrity-based bureaucracy. Issues such as lateness, lack of responsibility, and weak supervision form the background of this research. Using a descriptive qualitative approach, data were collected through in-depth interviews, observations, and document analysis related to disciplinary regulations. The findings show that ASN work discipline is generally adequate, although weaknesses remain in punctuality and compliance with internal rules. Factors such as motivation, leadership role modeling, organizational culture, and internal supervision significantly influence disciplinary behavior. This study highlights the importance of continuous coaching, effective communication, and exemplary leadership as strategic efforts to sustainably improve ASN work discipline.